Optimal planning of diesel fuel consumption for the Amazonas pumping station of the heavy crude oil pipeline (OPC) Ecuador S.A. - Bermejo, Jenny (2021)
In the Amazonas station, the consumption and expenditure of diesel per year has been increasing as of 2018 due to the characteristics of the heavier crude that is being transported. On many occasions, diesel orders are not made with due anticipation, which means that shipments are not made from the nearest terminal, but from the one with fuel available at that time; This generates an increase in costs, due to the distance that the tank car must travel to the Amazonas station. Therefore, it is important that the OCP Company has an effective administration of fuel purchases, in the correct quantities, at the right prices, at the right time and on a continuous basis, which will contribute significantly to the economy of the Company.